PERCEPTION OF YOUNG STUDENTS ABOUT THE CULTURAL SPORTING PROJECT OF SANTA MONICA COLLEGE (Fiep Bulletin - online, 2013)
Santa Monica College, founded in 1937, located in North and West zones of the City of Rio de Janeiro, has four teaching units, in external and semi-internal systems, to boys and girls; it offers Education to levels up to high school. The cultural Sporting project, offered by this school, is to develop physical-sporting activities in the school and create Sporting teams, thus giving value to Physical Education. The goal of this study is to identify and analyze the perception of students of 6th and 7th years about the Project, to identify relations established by this Project in school culture and their possible influence in the way of life of students. The sample, of 142 students, represents 56,39% of the students of Cachambi unit. These students have been invited to write on their perceptions about Physical Education. Results show that it is in Physical Education classes that students acquire reference about the practice of physical-sporting activities in the school, thus directing their perceptions about the relevance of this practice. Following them, Physical Education has the responsibility of promoting health and social integration. They conceive extra-school program as a relevant opportunity for students, given the variety of activities offered, and the possibility offered for keeping active, by practicing physical activity.
Keywords: sporting cultural project; physical-sporting activities; young students